2021
DOI: 10.3390/biom11121916
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Hyaluronan Modulates the Functional Properties and Matrix Effectors Expression of Breast Cancer Cells with Different Estrogen Receptor Status

Abstract: Hyaluronan (HA) is an extracellular matrix glycosaminoglycan (GAG) that plays a pivotal role in breast cancer. While HA is the only GAG not normally substituted with sulfate groups, sulfated hyaluronan (sHA) has previously been used in studies with promising antitumor results. The aim of the present study was to evaluate the effects sHA fragments have on breast cancer cells with different estrogen receptor (ER) status. To this end, ERα-positive MCF-7, and ERβ-positive MDA-MB-231 cells were treated with non-sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…38 For example, downregulation of RHAMM or CD44, was observed in prostate cancer cell lines, resulting in a diminished PI3K/Akt signaling pathway. 12 Recently, Koutsakis et al 15 have demonstrated that sHA (similar to our sHA) modulates the expression of HA synthase but not CD44 in breast cancer cells. Finally, when we used an in vivo xenograft breast cancer model, we found a significant decrease in vascularization in tumors inoculated with Mo/MØ preincubated with sHA1 or sHA3.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…38 For example, downregulation of RHAMM or CD44, was observed in prostate cancer cell lines, resulting in a diminished PI3K/Akt signaling pathway. 12 Recently, Koutsakis et al 15 have demonstrated that sHA (similar to our sHA) modulates the expression of HA synthase but not CD44 in breast cancer cells. Finally, when we used an in vivo xenograft breast cancer model, we found a significant decrease in vascularization in tumors inoculated with Mo/MØ preincubated with sHA1 or sHA3.…”
Section: Discussionsupporting
confidence: 67%
“…As mentioned above, it was previously shown that sHA reduced tumor aggressiveness in several cancer models as bladder, prostate, and breast cancer. [12][13][14][15] However, no reports were found about action on tumor-associated cells, which was evaluated in our study. It is important to note that sHA action is dependent on sulfation degree, thus our first objective was to assess if the sHA1 and sHA3 sHA as LMW or fragments, with different sulfation degrees but similar MW range 30-60 kDa (around 60-100 monomers, see Table 1) affect the behavior of immune cells, Mo/MØ or EC associated to a tumor context.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…While HA is the only GAG not normally substituted with sulfate groups, several studies suggest that sulfated hyaluronan (sHA) exhibits promising antitumor results. Koutsakis et al show that sHA fragments attenuate breast cancer cell proliferation, migration, and invasion while increasing adhesion on collagen type I in a manner related to their estrogen receptor (ER) status [2]. Furthermore, sHA modulates the expression of epithelialto-mesenchymal transition (EMT) markers and downregulate matrix remodeling enzymes such as the matrix metalloproteinases (MMPs).…”
Section: Hyaluronan In Breast Cancermentioning
confidence: 99%